Dampak Investasi Pertanian dan Non Pertanian terhadap Perekonomian Indonesia - Hairin Fajeri; Artahnan Aid; Abdullah Dja’far (Universitas Lambung Mangkurat, 2011)
The purpose of this study were: (1) analyze the factors that affect Gross Domestic Product, (2) determine the factors that influence agricultural and non agricultural investment to economic growth, and (3) analyze the impact of investment in agriculture and non agricultural in reducing the unemployment. Simultanous equation was used by involving four endogen variables and theree exogen one. The results showed that Gross Domestic Product (GDP) was affected by previous year of investment on agriculture (LPR), investment on non-agriculture (NPR), workforce-labor ratio (TK1), economic crisis, time trend and previous year GDP. Investment on agriculture (PR) was affected by changes in GDP, the ratio of wages per worker with total wages, time trends and the previous PR. Furthermore, NPR was influenced by the previous GDP, interest rates, exchange rate, economic crisis and time trend. Moreover, unemployment is affected by the change PR, NPR, UMPR previous years, the time trend and previous year of unemployment.The research also found that the investment on the agricultural sector reduced unemployment more than the non-farm sector investments did. Thus, agriculture sector should be emphasized in order to promoting economic growth and reducing the unemployment.